Legislation Improvement of Consumers Rights Defense - N. A. Rezina; L. V. Ivanova (Сибирское юридическое обозрение, 2013)
The article deals with some problems of consumers crediting. The question analyzed concerns the possibility of the RF Law norms application “On the Defense of Consumers Rights” in terms of credit legal relationships.